2013
DOI: 10.1002/pola.26908
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of naphtho[2,1-b:3,4-b′]dithiophene-based polymers with extended π-conjugation systems for use in bulk heterojunction polymer solar cells

Abstract: Two novel polymeric semiconductor materials based on naphtho[2,1‐b:3,4‐b']dithiophene (NDT), PNDT‐TTT and PNDT‐TET, were designed and synthesized. These synthesized polymers were tested in bulk heterojunction solar cells as blends with the acceptor [6,6]‐phenyl‐C71‐butyric acid methyl ester (PC71BM). PNDT‐TTT contained tri‐thiophene units, and PNDT‐TET contained bi‐thiophene units coupled by ethylenic linkages. Comparison to the properties of PNDT‐T, which contained single thiophene units, these polymers exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…These results are based on the papers previously reported by our group 16. 17 From Figure 7 a, it can be found that PNDT ‐ T solution exhibits two maximum absorption peaks ( λ max ) at λ= 523 nm and 555 nm whereas the λ max for PNDT ‐ TTT is redshifted slightly to λ= 539 nm and 578 nm, due to the longer π‐conjugation length in the PNDT ‐ TTT polymer 17. Compared with the two polymers, PNDT ‐ TT solution exhibits a further redshifted absorption profile, which can be ascribed to the stronger intermolecular stacking in the PNDT ‐ TT polymer 29.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…These results are based on the papers previously reported by our group 16. 17 From Figure 7 a, it can be found that PNDT ‐ T solution exhibits two maximum absorption peaks ( λ max ) at λ= 523 nm and 555 nm whereas the λ max for PNDT ‐ TTT is redshifted slightly to λ= 539 nm and 578 nm, due to the longer π‐conjugation length in the PNDT ‐ TTT polymer 17. Compared with the two polymers, PNDT ‐ TT solution exhibits a further redshifted absorption profile, which can be ascribed to the stronger intermolecular stacking in the PNDT ‐ TT polymer 29.…”
Section: Resultsmentioning
confidence: 81%
“…The details of the syntheses have been reported previously 16. 17 The three polymers were soluble in commonly used chlorinated solvents such as chloroform, chlorobenzene, and o ‐dichlorobenzene (the solubility of the PNDT ‐ T , PNDT ‐ TT , and PNDT ‐ TTT was 13, 10, and 12 g L −1 , respectively.). Phenyl‐C 71 ‐butyric acid methyl ester (PC 71 BM), the fullerene derivative (99.5 %) used as the electron acceptor, was obtained from Nano‐C.…”
Section: Methodsmentioning
confidence: 99%
“…PNDT‐B showed ambipolar characteristics while PNDT‐TBT showed p‐type character is 100 times better than n‐type character. In addition, both polymers with D‐A structure showed similar or lower mobility compared with PNDT‐T and PNDT‐TT with D‐D structure . Thus, it is carefully suggested that backbone planarity of polymer is more important than D‐A interaction in PNDT‐derivatives.…”
Section: Resultsmentioning
confidence: 96%
“…The chemical structures and synthetic routes to the new polymers are shown in Scheme . NDT was synthesized by thiophene‐centered oxidative cyclization according to previously reported procedures . PNDT‐B was synthesized by a Suzuki reaction of 2,9‐dibromo‐4,5‐bis(2‐octyldodecyloxy)naphtho[2,1‐b:3,4‐b′]dithiophene and 4,7‐bis(4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolan‐2‐yl)benzo[c][1,2,5]thiadiazole.…”
Section: Resultsmentioning
confidence: 99%
“…Becke's three parameter gradient corrected functional (B3LYP) with a polarized 6-31 G** basis was used for full geometry optimization. Methyl alkyl groups were used in place of the bulky alkyl substituents to limit computation time, since they do not significantly affect the equilibrium geometry and thus the electronic properties [25]. As depicted in Fig.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%